PENGARUH SIKAP BELAJAR TERHADAP HASIL BELAJAR PADA MATA PELAJARAN EKONOMI DI SMA ISLAMIYAH PONTIANAK. - Nadira Sahara; Mashudi Mashudi; Bambang Genjik (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThe research aims to find out the effect of a student's learning attitude on the results ofstudying at class XI Social 1 on economic subject at the islamiyah senior high schoolPontianak. The method used in this research is a quantitative descriptive method withrelationship study forms. The sample in this research is all the students in the class is1 to 25 students. The data collection used is direct communication (teachers andstudents), indirect communication (questionnaires) and the documentary research(student value data). With formulation y = 62,573 + 0.12 2x. Based on the SPSS 16.0,t counted 2.474, whereas t table with 25 respondents had a degree in df = n - 2 or 25-2 = 23, therefore t table was 2.069, from which results compared with t results fromthe table. Created that t count > t tables (2.474 > 2,069) so that ha is accepted and hois rejected. Coefficient determinations from research indicate the contribution ofinfluence between free and variable variables bound by 0.210 or 21%, while the rest isaffected by other factors. So it concluded that there was an effect of a student'slearning on a student's study in the economic subjects of the class XI Social 1 at theislamiyah senior high school Pontianak.Keywords: Learning Attitude, Learning Result